THE USE OF COORPERATIVE LEARNING MODELS IN NATURAL SCIENCE EDUCATION - Aang Andi Kuswandi (Universitas Maritim AMNI Semarang, 2023)
The purpose of this research is to determine the impact of the cooperative learning approach in science education. Cooperative learning can help students make significant strides in building attitudes, beliefs, and behaviors that will allow them to participate in their communities in ways that are congruent with the goals of historical education. The research data is in the form of numbers derived from tests and observation outcomes (direct observation). Teachers and students in the scientific learning process were used as data sources in this study by employing identity cards. The first instrument used in this study was self-research, which served as a data collector with the help of supporting instruments in the form of observation sheets.